Finite-element design of concrete structures : practical problems and their solutions - Rombach, G. A. (ICE, 2011)
"An increasing reliance on computer power means that now even simple structures are designed with the aid of computers. In this book, the author uses worked examples of real-life structures to address the dangers of a blind acceptance of computer outputs. Illustrating the difference between theory and practice, and the importance of practical knowledge of the behaviour of a structure, this book will help readers to eliminate errors in their calculations."--Publisher.
Keywords: Concrete construction.; Concrete bridges -- Design and construction.; Architecture.; Computer-aided design.; elektronické knihy; electronic books